2007
DOI: 10.1002/art.22556
|View full text |Cite
|
Sign up to set email alerts
|

Excreted urinary mediators in an animal model of experimental immune nephritis with potential pathogenic significance

Abstract: Objective. Currently, proteinuria is viewed as the earliest indicator of renal disease in immune-mediated nephritis. The objective of this study was to determine whether additional mediators may be excreted in the urine during immune-mediated nephritis, using an experimental model with a well-defined disease course.Methods. Urine samples from mice with antiglomerular basement membrane (anti-GBM) antibodyinduced experimental nephritis were screened using a focused immunoproteome array bearing 62 cytokines/ chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 38 publications
2
43
0
Order By: Relevance
“…Hence, this represents the first report of elevated urinary sTNFR-1 in lupus nephritis. However, urinary TNFR-1 in murine and human lupus nephritis may be originating from the serum at least in part, based on our findings, consistent with our findings in the experimental anti-glomerular basement membrane (GBM) model (20).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Hence, this represents the first report of elevated urinary sTNFR-1 in lupus nephritis. However, urinary TNFR-1 in murine and human lupus nephritis may be originating from the serum at least in part, based on our findings, consistent with our findings in the experimental anti-glomerular basement membrane (GBM) model (20).…”
Section: Discussionsupporting
confidence: 91%
“…Likewise, it has been suggested that glomerular disease may be amenable for therapy by blocking P-selectin (42). Based on our Ab blocking studies in the experimental anti-GBM nephritis model, CXCL16 may turn out to be yet another therapeutic target in nephritis (20). Finally, it remains to be seen whether the coordinate blocking of one or more of these molecules may offer therapeutic relief that is even more superior in lupus nephritis.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations